2022
DOI: 10.1029/2021jd036379
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Patterns of Soil Nitrous Acid Emissions and Their Acceleration of Rural Photochemical Reactions

Abstract: Abiotic and biotic releases of nitrous acid (HONO) from soils contribute substantially to the missing source of tropospheric HONO and hydroxyl radicals (OH). However, global and regional patterns of soil HONO emissions are rarely quantified, and the contributions of such emissions to atmospheric oxidization capacity are unclear. Here, we present that the best estimate of global soil HONO emissions in 2017 was 9.67 with a range of 7.36–11.99 Tg N yr−1, and cropland soils accounting for ∼79%. The analyses also i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…The maximum emission of HONO in our national samples ranged from 0.2 to 484 ng m –2 s –1 . The range is wider than the range of five samples in Xinjiang (5–250 ng m –2 s –1 ) and of 35 samples in Shanghai (4–288 ng m –2 s –1 ), highlighting large variations of soil HONO emissions from the vast land of China. Resulting from the high N deposition in China, the maximum HONO emissions from forest soils in this study (range of 0.2–208 ng m –2 s –1 , mean of 50 ng m –2 s –1 ) are higher than those from forest soils in Germany (<1.2 ng m –2 s –1 ), Australia (<5 ng m –2 s –1 ), Suriname (<5 ng m –2 s –1 ), and Finland (0–1 ng m –2 s –1 ) .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The maximum emission of HONO in our national samples ranged from 0.2 to 484 ng m –2 s –1 . The range is wider than the range of five samples in Xinjiang (5–250 ng m –2 s –1 ) and of 35 samples in Shanghai (4–288 ng m –2 s –1 ), highlighting large variations of soil HONO emissions from the vast land of China. Resulting from the high N deposition in China, the maximum HONO emissions from forest soils in this study (range of 0.2–208 ng m –2 s –1 , mean of 50 ng m –2 s –1 ) are higher than those from forest soils in Germany (<1.2 ng m –2 s –1 ), Australia (<5 ng m –2 s –1 ), Suriname (<5 ng m –2 s –1 ), and Finland (0–1 ng m –2 s –1 ) .…”
Section: Resultsmentioning
confidence: 77%
“…Soil emissions are an important source of reactive nitrogen (N) species in the atmosphere, which strongly influence atmospheric chemistry, air pollution, and climate. , It has long been known that soil microbial activities can emit nitric oxide (NO), which account for approximately 20% of total global emissions of nitrogen oxides (NO x ). This can increase to 40% in agricultural regions during periods in which fertilizers are applied to soils, resulting in a significant increase in concentrations of NO x and ozone (O 3 ). Recent research has revealed that similar soil microbial activities also emit nitrous acid (HONO). Photolysis of HONO is an important source of hydroxyl radicals (•OH), which are the main atmospheric oxidant initiating the production of O 3 and secondary aerosols. However, few studies have quantified the HONO emissions of diverse soil types worldwide. ,, The most comprehensive study thus far measured HONO and NO emissions from 17 soil samples collected from various regions worldwide, including five samples collected from the Xinjiang region in northwestern China …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to identify these for CO 2 fluxes used an artificial intelligence approach with pairs of eddy covariance sites at differing distances (Reed et al, 2021). Wu et al (2022) evaluated bottom-up scaling across multiple products for global soil nitrous acid (HONO) emissions. Levy et al (2022) reviewed the key challenges for upscaling when it comes to the UK greenhouse gas program and finds an essential role for uncertainty propagation, a factor also evaluated for gross primary productivity upscaling by Xie et al (2022).…”
Section: A Scale For All Silosmentioning
confidence: 99%
“…Wu et al. (2022) evaluated bottom‐up scaling across multiple products for global soil nitrous acid (HONO) emissions. Levy et al.…”
Section: A Scale For All Silosmentioning
confidence: 99%